Pengaruh Pemanfaatan Layanan dan Strategi Promosi GoFood terhadap Kinerja Penjualan UMKM Kuliner di Surabaya: Peran Keunggulan Bersaing Digital - Wasiun Nabil; Dhiyan Septa Wihara (Indonesian Journal of Islamic Economics and Business, 2026)
The rapid growth of digital food delivery platforms such as GoFood has opened new opportunities for culinary micro, small, and medium enterprises (MSMEs) to expand their market reach and increase sales. However, not all business owners are able to optimize the available services and promotional strategies, resulting in varying levels of sales performance. This study aims to analyze the effect of GoFood service utilization and promotional strategies on the sales performance of culinary MSMEs in Surabaya, with digital competitive advantage as a mediating variable. A quantitative approach was employed using purposive sampling, involving 100 culinary MSME owners or managers who had been GoFood partners for at least six months. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that service utilization and promotional strategies have a positive and significant effect on both digital competitive advantage and sales performance. However, digital competitive advantage does not significantly affect sales performance and fails to mediate the relationship between service utilization or promotional strategies and sales performance. These findings suggest that sales performance improvements are more directly driven by the optimization of GoFood services and promotional strategies rather than through the formation of digital competitive advantage. This study contributes to the digital marketing management literature by integrating platform service utilization and promotional strategy variables with the concept of digital competitive advantage as a mediator, offering practical implications for MSMEs seeking to optimize their use of digital platforms more effectively and strategically.